2000
DOI: 10.1038/sj.ijo.0801381
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopamine D2 receptor polymorphisms Ser311Cys and TaqIA with obesity or type 2 diabetes mellitus in Pima Indians

Abstract: OBJECTIVES: To investigate whether (a) variants within the dopamine D2 receptor gene (DRD2) are associated with obesity and type 2 diabetes in Pima Indians, and (b) whether variation in this gene could be responsible for previously observed linkage to these phenotypes, at chromosome location 11q23 ± 24, in this population. DESIGN: Two single nucleotide polymorphisms (SNPs), Ser311Cys and TaqIA, within the DRD2 gene were genotyped by allelic discrimination PCR in subjects who had provided evidence of linkage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 27 publications
(20 reference statements)
1
42
1
1
Order By: Relevance
“…However, the Ser311Cys mutation did not account for the linkage to BMI on chromosome 11 (14). Furthermore, in the smaller group of Pima Indians in the present study, we did not find differences in weight and percentage of body fat between genotypes (Tables 1 and 2).…”
contrasting
confidence: 36%
See 3 more Smart Citations
“…However, the Ser311Cys mutation did not account for the linkage to BMI on chromosome 11 (14). Furthermore, in the smaller group of Pima Indians in the present study, we did not find differences in weight and percentage of body fat between genotypes (Tables 1 and 2).…”
contrasting
confidence: 36%
“…We have recently reported that among Pima Indians, individuals with a Cys311-encoding allele have a higher BMI than those homozygous for the Ser311-encoding allele (14). However, the Ser311Cys mutation did not account for the linkage to BMI on chromosome 11 (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with genotypes containing either one or two copies of the A1 allele have fewer D2 receptors than have those lacking an A1 allele and so are associated with reduced brain dopamine signaling (Jonsson et al, 1999;Pohjalainen et al, 1998;Ritchie & Noble, 2003). In genetically homogeneous populations, such as the Pima Indians, a missense substitution in the DRD2 gene has been associated with reduced resting energy expenditure (Tataranni et al, 2001), greater BMI, and type II diabetes (Jenkinson et al, 2000). Epidemiological studies in genetically heterogeneous human populations have demonstrated a higher prevalence of the A1 DRD2 allele in obese individuals (~50%) compared with lean individuals (~30%; Blum et al, 1996;Comings et al, 1993;Comings, Gade, MacMurray, Muhleman, & Peters, 1996;Noble et al, 1994).…”
Section: Behavioral Genetics Of Food Reinforcementmentioning
confidence: 99%